How I met your mother. Season one [videorecording (DVD)] - Radnor, Josh, 1974-; Segel, Jason, 1980-; Hannigan, Alyson, 1974-; Harris, Neil Patrick, 1973-; Smulders, Cobie, 1982- (20th Century Fox Home Entertainment, 2006)
A love story in reverse: 'How I met your mother' is a comedy about Ted and how he fell in love. When Ted's best friends Marshall and Lily decide to tie the knot, it sparks the search for his own Miss Right. Helping him in his quest is his bar-hopping "wing-man" Barney, a confirmed bachelor with plenty of wild scemes for picking up women. Ted's sights are set on the charming and independent Robin, but destiny may have something different in mind. Told through a series of flashbacks, Ted recalls his single days, the highs and lows of dating and the search for true love.